Epitaxially Strained CeO2/Mn3O4 Nanocrystals as an Enhanced Antioxidant for Radioprotection. Issue 31 (10th June 2020) - Han, Sang Ihn; Lee, Sang‐woo; Cho, Min Gee; Yoo, Ji Mun; Oh, Myoung Hwan; Jeong, Beomgyun; Kim, Dokyoon; Park, Ok Kyu; Kim, Junchul; Namkoong, Eun; Jo, Jinwoung; Lee, Nohyun; et al.
Abstract: Nanomaterials with antioxidant properties are promising for treating reactive oxygen species (ROS)‐related diseases. However, maintaining efficacy at low doses to minimize toxicity is a critical for clinical applications. Tuning the surface strain of metallic nanoparticles can enhance catalytic reactivity, which has rarely been demonstrated in metal oxide nanomaterials. Here, it is shown that inducing surface strains of CeO2 /Mn3 O4 nanocrystals produces highly catalytic antioxidants that can protect tissue‐resident stem cells from irradiation‐induced ROS damage. Manganese ions deposited on the surface of cerium oxide (CeO2 ) nanocrystals form strained layers of manganese oxide (Mn3 O4 ) islands, increasing the number of oxygen vacancies. CeO2 /Mn3 O4 nanocrystals show better catalytic activity than CeO2 or Mn3 O4 alone and can protect the regenerative capabilities of intestinal stem cells in an organoid model after a lethal dose of irradiation. A small amount of the nanocrystals prevents acute radiation syndrome and increases the survival rate of mice treated with a lethal dose of total body irradiation. Abstract : Inducing surface strains of CeO2 /Mn3 O4 nanocrystals produces highly catalytic antioxidants that are powerful enough to protect intestinal stem cells from irradiation‐induced reactive oxygen species damage. Only a small dose of the CeO2 /Mn3 O4 nanocrystals prevents acute radiation syndrome in a human intestinal organoid model and increases survival rate of mice treated with a lethal dose of total body irradiation.